Gilberto Mendes : homem novo, música nova - Palermo Filho, Silas da Luz (2016)
This research approaches the person of Gilberto Mendes as a transforming himself and consequently his art starting from a perception of the world and the necessary significance to him. Mendes's work is intertwined with your personal perspective and new thinking, a new man before a new world. His artistic practice is therefore a process of (re) signification of self and musical signs; its influence to the contemporary art world is renowned for artists and for the beginners of this generation. Thus, this work presents a profile of the thought of Gilberto Mendes transported to his work and ultimately how it has influenced, has left a legacy both artistic, of inventor that was, as academic. Research is on to describe, analyze and compare the artistic process of Mendes and draw implications of this. The use of some writings and musical language materials are needed in such a task to make it objective and corroborative, observing techniques, historical and social issues. The research contributes to a better understanding of contemporary art in the contemporary, music specifically, where language and technology are strongly present and dynamic; also shows the solution given by Mendes for a new art, and paid off the other composers and academics.